Analysis of motivative components of sexual behavior in man with chronic prostatitis - Krivitsky, V. O. (Journal of Education, Health and Sport, 2017)
The objective: to analyze the motivational component of sexual behavior in chronic prostatitis (CP) men. 109 CP patients were examined. The clinical picture of CP in all persons under examination was accompanied by impaired sexual function, in 70 (64.2%) patients it was presented with variations of erectile dysfunction (ED), in 39 (35.8%) – with combined lesions of erectile and ejaculatory function. Preliminary sexual examination allowed to establish that all of the examined had disorders of the rate of psychosexual development, and patients with ED were diagnosed with simple forms of asynchrony, which were formed due to the isolated action of one somatogenically conditioned factor, and in patients with sexual intercourse the emergence of which was facilitated by the combined action of several pathogenic factors. ED and simple forms of asynchrony of psychosexual development persons formed study group 1 (group 1), and patients with combined sexual dysfunction and combined forms of asynchrony formed group 2 (group 2). Motivational models of sexual behavior inherent in CP men was identified. Persons with pattern-regulated, homeostabilizing and passive-submissive types of sexual motivation, the leading motive for sexual activity for which was the duty fulfillment, were attributed to the template-stereotype model (37.1% of group 1 and 30.8% of group 2, p> 0.05). Men with a promotional model had pattern-regulated and passive-submissive sexual motivation, and the realization of reproductive function as a leading motive for sexual life (18.6% of group 1 and 30.8% of group 2, p <0.05). The compensatory model of sexual behavior united individuals with aggressive selfishness, genital and passive-submissive types of sexual motivation with a leading motive for using sexual relations as a means of self-affirmation (14.3% of group 1 and 17.9% of group 2, p> 0.05). Recreational models were matched by a mutually altruistic communicative-hedonic sexual motivation with the desire to reach orgasm and to enjoy the partner as a motive for sexual activity (12.9% of group 1 and 12.8% of group 2, p> 0.05). The communication motivational model was characterized by sexual motivation and communication as a motive for sexual intercourse (12.9% of group 1 and 5.1% of group 2, p <0.05). The least represented was the relaxation model of sexual behavior, which united individuals with a homeostabilizing type of sexual motivation and motive for sexual intercourse as a means of relaxation (4.3% of group 1 and 2.6% of group 2, p> 0.05). The data obtained need to be taken into account when constructing a scheme of complex treatment of patients with CP.